Evaluation of irradiation effects on the microstructure and properties of Ag-sheathed Bi-2212 superconducting round wire for future application in CFETR. (7th October 2020) - Li, Zuoguang; Zhu, Hongmei; Qiu, Changjun; Yang, Dongsheng; Qin, Jinggang; Zhou, Chao
Abstract: The Chinese Fusion Engineering Test Reactor (CFETR) is designed to build a fusion engineering Tokamak reactor generating fusion power of 200–1500 MW, and to test the breeding tritium during fusion reaction. This may require a maximum magnetic field up to 15 T in the central solenoid and toroidal field coils. New superconducting materials should be developed for satisfying the next-generation fusion reactors with critical requirements. Recently, Bi2 Sr2 CaCu2 Ox (denoted as Bi-2212) is considered as one of the most promising potential superconductors to be used as the magnets in CFETR, however, they will be subjected to harsh irradiation under operating conditions. The irradiation effects of the high-energy helium ions on the Ag-sheathed Bi-2212 superconducting round wire have been explored for the first time in this work. The microstructure and the critical current at 4.2 K of the superconducting wire before and after irradiation have been carefully investigated. Room-temperature x-ray diffraction (XRD) profiles showed that all the peaks shifted rightward significantly with a broadened (111)Ag peak, indicating that the high-energy He + irradiation resulted in appreciable defects and strain in the superconducting wire. Meanwhile, the in-situ high-temperature XRD tests showed that the lattice constant and the thermal expansion coefficient were deduced in the irradiated sample to be due to the presence of the generated defects. After irradiation, the grain size of the Ag sheath was refined, and the lattice of Bi-2212 superconductor was distorted obviously, as confirmed by transmission electronic microscopy. The critical current IC at 4.2 K of the superconducting wires in the field of 0–12T determined by the four-probe technique, decreased substantially after irradiation because of the lattice distortion and the consequently induced strain in the Bi-2212 superconductor. This work provides a solid basis for evaluating and understanding the irradiation effects upon the Ag-sheathed Bi-2212 superconducting wire, more promising for future application in CFETR.